Dodecacyclic‐Fused Electron Acceptors with Multiple Electron‐Deficient Units for Efficient Organic Solar Cells. Issue 17 (11th May 2021) - Ma, Shanshan; Feng, Hexiang; Liu, Xiang; Hu, Zhicheng; Yang, Xiye; Liang, Yuanying; Zhang, Jie; Huang, Fei; Cao, Yong
Abstract: Fused aromatic cores in non‐fullerene electron acceptors (NFEAs) play a significant role in determining their optoelectronic properties and photovoltaic performance. In this work, a dodecacyclic‐fused core with three electron‐deficient units is synthesized through a double intramolecular Cadogan reduction cyclization. Terminal groups with different halogen substitution (F or Cl) are grafted onto the dodecacyclic‐fused core to afford MS‐4F and MS‐4Cl, both of which showed strong and broad absorption, narrow bandgaps around 1.40 eV, and variable molecular packing model in pristine and blend films. Photovoltaic performance of solar cells containing MS‐4F and MS‐4Cl as NFEAs were investigated with resultant power conversion efficiencies (PCEs) of 11.75 % and 11.79 %, respectively. The mechanism study indicates that both of PBDB‐T : MS‐4F‐ and PBDB‐T : MS‐4Cl‐based devices displayed high hole and electron mobility values, efficient charge transfer, and low charge recombination etc. These results indicate that designing multiple‐fused aromatic cores with multiple electron‐deficient units is a promising strategy to obtain high‐performance NFEAs. Abstract : Put 12 rings on it : Two non‐fullerene electron acceptors for organic solar cells have been developed, which consist of a fused dodecacyclic core with three electron‐deficient units and two terminal groups. Both MS‐4F and MS‐4Cl (see figure) show strong and broad absorption in the visible‐near‐infrared region, narrow bandgaps around 1.40 eV, and excellent photovoltaic performance.